2015
DOI: 10.1007/s13197-015-1980-3
|View full text |Cite
|
Sign up to set email alerts
|

Sprout suppression on potato: need to look beyond CIPC for more effective and safer alternatives

Abstract: World over, potatoes are being stored at [8][9][10][11][12]. This is the most common way of long-term (up to 6 to 9 months) storage of potatoes. The benefit of storing the potatoes within the temperature range of 8-12°C is minimum accumulation of sugars in stored potato tubers. In sub-temperate, sub-tropical and tropical countries of the world, short-term (3 to 4 months) storage of potatoes is being done by non-refrigerated traditional/on-farm methods. These short-and long-term storage methods keep the stored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 88 publications
0
65
0
12
Order By: Relevance
“…Burton [40] estimated that respiration of potatoes increases by 50% if sprouts reach 1% of tuber weight. It has been found that the sprout growth equivalent to 1% increase in the tuber surface area can lead to doubling of the moisture loss from the tubers [41]. In the second year of our study (2018), the start of sprouts growth (peeping) was observed from the sixth month of storage, which might be the reason for slight to medium increase of weight loss of all four varieties during the last stage of storage ( Figure 5).…”
Section: Warmer Wound-healing Temperature Resulted In Less Weight Losmentioning
confidence: 55%
“…Burton [40] estimated that respiration of potatoes increases by 50% if sprouts reach 1% of tuber weight. It has been found that the sprout growth equivalent to 1% increase in the tuber surface area can lead to doubling of the moisture loss from the tubers [41]. In the second year of our study (2018), the start of sprouts growth (peeping) was observed from the sixth month of storage, which might be the reason for slight to medium increase of weight loss of all four varieties during the last stage of storage ( Figure 5).…”
Section: Warmer Wound-healing Temperature Resulted In Less Weight Losmentioning
confidence: 55%
“…Therefore, storage is an essential post-harvest activity that must be undertaken by farmers in case the crop cannot be immediately availed to prospective markets. According to [3], storage of potatoes is associated with various challenges such as sprouting and accumulation of sugars. Consequently, there is a need to store the tubers under specific conditions to reduce loss.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a need to store the tubers under specific conditions to reduce loss. While the produce is mostly stored at 8-12 • C (85%-90% RH) temperatures around the world, such conditions favor sprouting and sprout growth once the period of natural dormancy is over, hence the need for an effective sprout suppressant [3].…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of CIPC in the fabric of a building previously used for storing potatoes is therefore now essential, prior to storage of other commodities, as the presence of CIPC may render it unfit for storage (Red Tractor Assurance b 2014). Also, the maintenance of accurate records pertaining to buildings with a history of CIPC use is crucial for preventing cross contamination of crops that have no clearance for CIPC (AHDB-Potatoes 2012), which is a recommendation that the Potato Industry CIPC Stewardship Group has supported since its establishment in 2008 (Paul et al 2016).…”
Section: Introductionmentioning
confidence: 99%